Children’s Internet use and physical and psychosocial development - Novaković, Svetlana; Milenković, Sanja; Srećković, Marijana; Backović, Dušan; Ignjatović, Vladimir; Capo, Nataša; Stojanović, Tamara; Vukomanović, Vladimir; Sekulić, Marija; Gavrilović, Jagoda; Vuleta, Katarina; Ignjatović, Vesna (Frontiers in Public Health, 2023)
Abstract Introduction: Internet use (IU) commonly refers to sedentary lifestyle and may be addictive, especially among children. The aim of this study was to investigate the relationship between IU and some aspects of child physical and psychosocial development. Methodology: We conducted a cross-sectional survey by using a screen-time based sedentary behaviour questionnaire and Strengths and Difficulties Questionnaire (SDQ) – among 836 primary school children in the Braničevo District. The children's medical records were analysed for vision problems and spinal deformities. Their body weight (BW) and height (BH) were measured and body mass index (BMI) was calculated as BW in kilograms divided by BH in meters squared (kg/m2). Results: The average age of respondents was 13.4 (SD 1.2) years. The mean duration of daily Internet use and sedentary behaviour was 236 (SD 156) and 422 (SD 184) minutes, respectively. There was no significant correlation between daily IU and vision problems (near sightedness, farsightedness, astigmatism, strabismus), and spinal deformities. However, daily Internet use is significantly associated with obesity (p<0.001) and sedentary behaviour (p=0.01). There was significant correlation between emotional symptoms with total Internet usage time, and total sedentary score (p<0.001 for both, r=0.141 and r=0.132 respectively). There was a positive correlation between the total sedentary score of children and hyperactivity/inattention (r=0.167, p<0.001), emotional symptoms (r=0.132, p<0.001), and conduct problems (r=0.084, p<0.01). Conclusion: In our study, children’s Internet use was associated with obesity, psychological disturbances and social maladjustment.